2021
DOI: 10.1371/journal.pone.0250936
|View full text |Cite
|
Sign up to set email alerts
|

The use of digital texture image analysis in determining the masticatory efficiency outcome

Abstract: The mixture level of gum samples consisting of two colours can be assessed visually, using the electronic colorimetric method, employing digital image processing techniques and specially designed software. The study investigates the possibility of an alternative method called “digital texture image analysis” (DTIA) to assess improvement of masticatory efficiency in denture wearers. The objectives were i) to evaluate whether DTIA discriminates changes in the colour mixing ability within a group over time; ii) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Chewing ability can be assessed either subjectively, as a self-reported individual perception and satisfaction with mastication (using questionnaires and interviews), or objectively, based on different clinical chewing tests where changes of natural food or artificially produced test specimens are evaluated [ 6 ]. Simpler, faster, and more hygienic method for the analysis of changes among chewed test food particle size is the computer-assisted image processing [ 7 , 8 , 9 ]. Subjective patient-reported outcome measures (PROMs), which are extremely important in evidence-based dentistry, include validated questionnaires or interviews for evaluation of a self-perceived masticatory function from the patient's perspective, some of them taking into account only the domain of chewing, while others include social and psychological factors [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chewing ability can be assessed either subjectively, as a self-reported individual perception and satisfaction with mastication (using questionnaires and interviews), or objectively, based on different clinical chewing tests where changes of natural food or artificially produced test specimens are evaluated [ 6 ]. Simpler, faster, and more hygienic method for the analysis of changes among chewed test food particle size is the computer-assisted image processing [ 7 , 8 , 9 ]. Subjective patient-reported outcome measures (PROMs), which are extremely important in evidence-based dentistry, include validated questionnaires or interviews for evaluation of a self-perceived masticatory function from the patient's perspective, some of them taking into account only the domain of chewing, while others include social and psychological factors [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the Hubba-Bubba Tape chewing gum and by the ViewGum Software, Halazonetis et al ( Halazonetis, Schimmel et al, 2013 ) and Chawisa et al ( Chawisa Thangjittiporn, 2021 ) reported respectively 0.144 ± 0.082 and 0.051 ± 0.024. Lemić et al ( Milić Lemić, Rajković et al, 2021 ) reported, also, near values (0.063 ± 0.025) with Five Tape sugarless chewing gum.…”
Section: Discussionmentioning
confidence: 84%
“…The variance of hue serves as a measure for the level of color mixture, indicating better color mixing and improved chewing efficiency when the hue variance is lower. ( Milic, Rajkovic et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This first sweep was conducted automatically by the application of search filters and identification of exclusion terms in the advanced search interface of PubMed. After an initial screening from both scholars, 24 additional articles were excluded, including seven reviews or surveys [12,19,[34][35][36][37][38], seven describing workflows that required preexisting dentures [39][40][41][42][43][44][45], one not referring to digital workflows in clinical practice [46], four analyzing material properties [47][48][49][50] and five laboratory studies [51][52][53][54][55]. Next, 10 articles were eligible for full text analysis, of which one was excluded because of insufficient classification between CDs and overdentures [56], and one because it was a technique presentation accompanied with clinical pictures without any presentation of the cases [57]).…”
Section: Resultsmentioning
confidence: 99%